Salinity tolerance screening of traditional mangoes: Analysis of physiological and biochemical traits for abiotic stress tolerance - Bindu , B; Shelvy , S (Plant Science Today, 2025)
The study investigates the salinity stress tolerance of 34 traditional mango accessions from South Kerala. Salinity is a major abiotic stress limiting mango cultivation, especially in coastal and irrigated regions where salt accumulation in soil and water adversely affects growth, yield and fruit quality. Traditional mango varieties, being locally adapted and genetically diverse, may possess inherent tolerance mechanisms that enable survival under saline conditions. Screening these varieties for salinity tolerance through physiological and biochemical traits provides valuable insights for identifying tolerant genotypes. Key parameters such as chlorophyll content, relative water content, electrolyte leakage, proline accumulation and antioxidant enzyme activity serve as indicators of stress response and adaptive potential. Understanding these traits helps in assessing varietal differences in osmotic adjustment, ion regulation and oxidative stress management. The experiment observed significant increases in glycine betaine, proline and total soluble sugar levels under salinity stress, with accession KLM10 exhibiting the highest GB content. Enzymatic antioxidant varied significantly among accessions, with KLM12 displaying the highest catalase activity. The analysis of total chlorophyll content indicated that KLM10 maintained the highest chlorophyll levels under stress. The salinity tolerance index was highest in KLM10. A moderate positive correlation was found between total phenol content, chlorophyll content and TI, suggesting these parameters as potential markers for salinity tolerance. The study of traditional mangoes under salinity stress thus contributes to the selection and conservation of tolerant cultivars, facilitating sustainable mango production and genetic improvement programs aimed at enhancing abiotic stress tolerance.